Giving Gifts to Public Officials: A Comparative Analysis of Islamic Law and Indonesian Anti-Corruption Law - Ilgafur Tanjung (Haqqiyyah: Journal of Islamic and Legal Studies, 2025)
As usual gifts given to officials/employees, the intention of the giver cannot be separated from one of two things, namely: the gift giver aims to win the hearts of officials/employees so that they can get convenience and relief in every matter both at that time and in the future. And the giver of the gift who does give it on the basis of affection and does not expect anything in return, either material or service. This study examines the regulation of gift-giving to public officials from the perspectives of Islamic law and Indonesian Law No. 20 of 2001 on corruption. The result of this discussion is that gifts are given to officials/employees because their work and legal position are haram for those who give and receive as prohibited by Islam and the Law. The basis of the haram and impermissibility of the gift is the non-realization of equal rights between fellow human beings, both individuals and social. As for gifts given to employees or officials not because of their work and position, the law is permissible for both the giver and the receiver. Especially if the giver intends to strengthen the bond of friendship and strengthen relationships between others.